2004
DOI: 10.1088/0953-2048/17/8/024
|View full text |Cite
|
Sign up to set email alerts
|

1:2:3 superconductors (MxLax)(LauBau)2Cu3Oywith M = Ca or Y: lattice constants andTc

Abstract: The effect of a substitute ion on the lattice constants and Tc of the optimal oxygen doped (MxLa1−x)(LauBa1−u)2Cu3Oy has been studied. This series is variously called CLBLCO, CLBCO or CaLaBaCuO when M = Ca2+, or YLBLCO when M = Y3+. We found that the lattice constants depend linearly on x and u. The size of M is the main contributor that affects the lattice constant a, while its valence mainly influences the lattice constant c. The size and valence of the ions located on the Ba-site have no significant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In this case, a long annealing time is not necessary and in fact we found that a long time is no help in improving the superconducting transition temperature. To obtain relatively high transition temperatures in thin films, we believe that a suitable quenching method is a good choice with reference to our studies and a series of previous studies [1][2][3][4][5][6][7][8][9][10][11]. The importance is that previous studies suggested a quenching method that led to maintaining the equilibrium oxygen content and the homogeneity of its distribution.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…In this case, a long annealing time is not necessary and in fact we found that a long time is no help in improving the superconducting transition temperature. To obtain relatively high transition temperatures in thin films, we believe that a suitable quenching method is a good choice with reference to our studies and a series of previous studies [1][2][3][4][5][6][7][8][9][10][11]. The importance is that previous studies suggested a quenching method that led to maintaining the equilibrium oxygen content and the homogeneity of its distribution.…”
Section: Resultsmentioning
confidence: 81%
“…The relatively large rms roughness in figure 2(b) is due to the distribution of several large precipitation particles (for which the peak heights are in the range 20-100 nm) in the surface that is studied. One of the origins of the particles is probably due to off-stoichiometry in the local regions, since foreign phases can be with x = 0.5 samples, as mentioned in the literature [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The substitution of various rare earths for Y leaves the compound isostructural and isoelectronic, with general superconductivity with T c ∼ 90 K [1][2][3]. However, the substitution of trivalent elements such as La at a Ba-site results in an orthorhombic-to-tetragonal phase transition and destruction of T c [4][5][6][7]. The destruction of T c is attributed to the decrease in hole concentration caused by the introduction of donor electrons when La 3+ is substituted for Ba 2+ .…”
Section: Introductionmentioning
confidence: 99%